Intelligent physical activity versus modified behavioral activation in adolescent and young adult cancer patients with psychological distress: A randomized, controlled pilot trial. (18th July 2022) - Li, Lijun; Wang, Lu; Duan, Yinglong; Xiao, Panpan; Zhou, Yi; Luo, Xiaofei; Liu, Xiangyu; Xie, Jianfei; Cheng, Andy S. K.
Abstract: Background: More than 80% of adolescent and young adult cancer patients (AYACPs) experienced psychological distress. Physical activity and behavioral activation are effective to relieve the psychological distress in AYACPs. Methods: Participants aged 15–39 years diagnosed with malignant tumors were included. A total of 143 eligible AYACPs were randomly assigned to three groups. The treatment‐as‐usual group ( N  = 48) received routine care, the physical activity group ( N  = 47) received 8 weeks of physical activity program based on intelligent wearable devices, and the behavioral activation group ( N  = 48) received an internet‐based modified behavioral activation program for 8 weeks. Objective outcome measures included salivary cortisol and testosterone. Results: Linear mixed‐model analyses showed significant differences between treatment‐as‐usual, physical activity and behavioral activation in salivary cortisol, as well as total scores on depression and anxiety, physical activity, self‐efficacy, and social support. Significantly stronger effect sizes for physical activity group compared with behavioral activation group were found on physical activity ( d  = 0.53) (1 week after intervention), moderate activity ( d  = 0.61), and walking activity ( d  = 0.57) (3‐month follow‐up). Conclusions: Intelligent, wearable, device‐based physical activity program is more effective in alleviating anxiety and depression, reducing saliva cortisol, and improving physical activity in AYACPs than internet‐based modified behavioral activation program. Intelligent, wearable, device‐based physical activity program can reduce the time cost of AYACPs to ensure that the intervention is carried out. Abstract : This study combined the objective indicators (salivary cortisol) to explore the effect of an intelligent wearable device‐based physical activity program and internet‐based modified behavioral activation program on alleviating psychological distress in adolescent and young adult cancer patients (AYACPs) by a three‐arm RCT. The results demonstrated that an intelligent wearable device‐based physical activity program and internet‐based modified behavioral activation program can effectively alleviate anxiety and depression in AYACPs. Including objective evaluation metrics in psychological distress research is feasible.